Analisis Video Animasi Cerita Rakyat Riri sebagai Altenatif Pembelajaran Bahasa Indonesia Daring di Kelas IV Sekolah Dasar - Alfionita, Qinta Virya; Iswara, Prana Dwija; Iswara, Prana Dwija; Sunarya, Dede Tatang; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2021)
In an effort to improve online learning, teachers must find solutions to provide maximum learning.  This study focuses on the animation of the Riri's folktale using a qualitative descriptive method to describe the character values, the appropriateness of language according to the KBBI, the intrinsic elements, and the pedagogical values of the Riri's folktale animation videos. The results of the study (1) the aspect of character values from 18 character values, there are 16 character values in the Riri's folktale animation video;  (2) the aspect of appropriateness of language according to the KBBI there are 9 errors in the animated video of Riri's folktale;  (3) aspects of the intrinsic elements are in line with the provisions of that theme, plot, characterizations, background, and message;  (4) the pedagogical value aspect of the 9 pedagogical values, there are 4 pedagogic values so that it can be concluded that it is proper to be an alternative but cannot replace the role of the teacher in the learning process.